Il sito della Rocca di Oratino : dieci anni di ricerche : un'area funzionale all'aperto nell'età del Bronzo - Copat, Valentina (Archaeopress, 2022)
This volume presents excavation results pertaining to the final stages of occupation (late Subappennine period) of the Bronze Age site of Orantino-La Rocca (Campobasso), located in the upper Biferno river valley. These layers are marked by the presence of a series of cooking slabs and hearths, dedicated to food preparation and consumption.